The essentials of finance and accounting for nonfinancial managers - Fields, Edward (Financial consultant) (AMACOM, American Management Association, 2016)
This third edition of a popular crash course for managers helps you make sense of financial data, assess performance, and channel efforts into the most promising areas. Packed with the latest information on federal regulations, pertinent GAAP rules, global trends that can impact the financial picture, expanded case studies, and new practice exercises that reinforce the lessons and strengthen skills.
Keywords: Accounting.; Finance.; elektronické knihy; electronic books